Environmental Information: Pressures, Types, and Usage (Journal of Business Management and Accounting, 2016)
Global warming, manmade pollution, and pressure from various stakeholders are among the factors that drive business organisations to strike a balance in their  operations  by  reducing  negative  impact  on  the  environment  and  society, while increasing the company’s wealth. In response to these pressures, one common method is voluntary disclosure of information on environmental impact through  publication  of  corporate  social  responsibility  report.  The  majority  of studies on company’s environmental issues primarily look from the external viewpoint.  This  paper  takes  an  alternative  approach  focusing  on  processes  in relation to the management of environmental issues. Among the areas explored are pressure factors that lead managers to adopting sustainability management, the  types  of  environmental  information  being  considered,  its  usage,  and  the users. The findings derived from interviews with several key personnel revealed that  a  number  of  external  and  internal  pressures  lead  to  a  variety  of  internal users from different departments in the organisation.